Populism and international affairs: a comparison of Spain and Italy - Giurlando, Philip (Política. Revista de Ciencia Política, 2022)
This paper argues that, in the realm of international politics, populism contains thick ideological elements, and that identifying these elements can help us to make sense of their foreign policies preferences. It aims to support this argument with a focus on populists in Spain and Italy, namely Podemos, Vox, the 5SM, and the League. It also highlights how populists in both countries are constrained in implementing their vision due to the medium power status of their respective countries and their nations’ economic dependence on partners in the EU. The paper concludes with suggestions on future research.